From sponges to primates: emendation of 30 species nomina dedicated to the Swedish zoologist Einar Lönnberg - Koerber, Stefan (Zootaxa, 2009)
In 1891 Axel Johan Einar Lönnberg became a Doctor of Science and a Fellow of Zoology at the University of Uppsala. From 1904 to 1933, he served as head of the Vertebrate Department of the Royal Natural History Museum of Stockholm where after his expeditions around the world he worked the collected material himself. Although he was specialized in ornithology and the fauna of his homecountry Sweden, Lönnberg worked on so many different zoological groups “that since the days of Linnaeus hardly anyone has known so much about so many branches in zoology as Lönnberg” (Anonymous 1943). One of his special interests was to educate his Swedish countrymen about their native animals and he accomplished this during many years as editor and multiple author of the journal Fauna och Flora.